Impact of trade policy uncertainty on export products quality: New evidence by considering role of social capital - Hongguang Sui; Xijie Li; Ali Raza; Shihua Zhang (Journal of Applied Economics, 2022)
An increase in trade policy uncertainty raises policymakers' concerns, as it can be harmful to investments and growth globally. This study examines the impact of reducing trade policy uncertainty on export product quality. Based on the ASEAN-China Free Trade Area (ACFTA), the difference-in-difference, two-way fixed, and triple difference methods were used to conduct benchmark tests. The results show that reducing trade policy uncertainty improves export product quality. Social capital has strengthened the role of the changing trade environments. The results were robust after the PSM-DID, placebo test, and deletion of outliers. Furthermore, the role of social capital is incorporated into the regression model. From the perspective of informal internal systems, this study expands the theoretical view of regional trade integration research and answers the current trade strategy adjustment and export transformation policy concerns.
Keywords: 330; ASEAN-China FTA; export products quality; social capital; Trade policy uncertainty